Pursuing implementation solutions for targeted nitrogen management in agriculture– a novel approach to synthesize knowledge and facilitate sustainable decision making based on collaborative landscape modelling. (15th September 2019) - Christensen, Andreas Aagaard; Andersen, Peter Stubkjær; Piil, Kristoffer; Andersen, Erling; Vejre, Henrik; Graversgaard, Morten
Abstract: Regulation of nitrate emission from agriculture to aquatic environments in Denmark currently depend on general rules for nutrient application and associated farm-level reporting schemes. Similar or comparable centralized regulation instruments dedicated to controlling and limiting rather than focusing and improving N application practices exist in large parts of the OECD. Recent policy debates have exposed an array of problems relating to this type of regulation. Problems include issues of appropriate scale, transparency and failures to adapt intervention and regulation to relevant geo-ecological variations in contexts where general rules are being imposed on varied agro-ecosystems. Therefore it has been proposed to rescale regulation to better fit relevant socio-political and agro-environmental processes including the scale of farmers' decision making, the scale of relevant hydrological systems and the scale of key agro-ecological conditions such as soil characteristics and drainage. However, the challenge of shifting the regulation to a more local scale raises a number of questions. These include (1) How information produced locally can be integrated with national scale data? (2) In what way integrated datasets can used to model environmental effects of current and possible land use patterns? (3) In what way data and estimates of consequences of land use changes are best made available in decision making processes? To address these questions this article reports on ongoing work in Denmark to develop a decision support tool for N-management at the scale of agricultural landscapes, which are areas where a similar pattern of land use is repeated across the land surface, reflecting a specific mode of adapting agriculture to natural conditions. The aim of the article is to evaluate the design of a decision support tool aiming at enabling strategic N-management at landscape scales by linking decision support at the scale of individual farms with decision support targeted at groups of farms where a coordinated effort to solve common problems may be more efficient. Design targets for the tool were established empirically based on evidence from exploratory workshops with farmers and other stakeholders in 6 case areas across Denmark. On this basis a prototype GIS-tool for capturing, storing, editing, displaying and modelling landscape scale farming practices and associated emission consequences was developed. The tool was designed to integrate locally held knowledge with national scale datasets in live scenario situations through the implementation of a flexible, uniform and editable data model for land use data – the dNmark landscape model. Based on input data that is corrected and co-authored by workshop participants, the tool estimates the effect of potential land use scenarios on nutrient emissions. The tool was tested in 5 scenario workshops in case areas in Denmark in 2016, on the basis of which its design is evaluated and discussed in this article. Highlights: A participatory decision support tool was developed. The tool was tested in 5 watersheds in Denmark. Results indicate that community engagement and activation of local expertise may be critical to successful management of nitrogen emissions.